Influence of vertical-oriented vs. horizontal-oriented combined strength training in young basketball players - Sánchez-Sabaté, J.; Gutiérrez, H.; Marco-Contreras, L. A.; Younes-Egana, O.; Gonzalo-Skok, O.; Piedrafita, E. (The Journal of Strength and Conditioning Research, 2024)
This study aimed to compare the effects of 8-week combined vertical-oriented vs. horizontal-oriented training interventions in basketball athletes. Eighteen highly trained U-16 basketball players participated in this study and were randomly assigned to either a combined vertical-oriented training group (CVG, n = 9) or a combined horizontal-oriented training group (CHG, n = 9). Bilateral and unilateral vertical jump height, unilateral horizontal jump distance, 5-m, 10-m, and 20-m sprint times, change-of-direction sprint times, and a limb symmetry index were among the measured performance variables. Combined strength training was performed twice a week for 8 weeks. CVG was compounded by the squat exercise (3 sets of 6-8 R at 30-45% 1 repetition maximum [1RM]), jump squats (2 sets of 6 R, at 5-12.5% body mass [BM]), and vertical jumps (3-4 sets × 6 R). CHG included the hip thrust exercise (3 sets of 6-8 R at 30-45% 1RM), sled towing sprints (2-3 R, at 5-12.5% BM), and sprints (3-4 R of 20-m). Within-group differences showed significant (p < 0.05 and statistical power >80%) improvements in unilateral vertical jumping with the right leg after both training interventions. By contrast, only CHG improved 5-m, 10-m, and 20-m sprint times (p < 0.05 and statistical power >80%). Significant effects were observed for CHG compared with CVG in 5-m, 10-m, and 20-m sprint times (p < 0.05 and statistical power >80%). This study reinforces the importance of oriented-combined training based on force-vector specificity target, mainly in horizontal-oriented actions.